From TPACK to DPACK: The “Digitality-Related Pedagogical and Content Knowledge”-Model in STEM-Education - Thyssen, Christoph; Huwer, Johannes; Irion, Thomas; Schaal, Steffen (Education sciences, 2023)
Digitalization is a keyword in the discourse of educational science, but it is often linked to technological challenges, although digital changes occur throughout society. Therefore, STEM teachers are required to cope with technological changes in the subject, the increasing and diverse education and training technologies, and the ever-changing paths of information and communication of adolescents in their role as members of a changing society and culture. The TPACK-model focuses educators’ professional knowledge based on teachers’ expertise concerning technological knowledge per se and the pedagogy and content of their subjects. In contrast, knowledge relevant to daily life and social and cultural interaction beyond this is not clearly included in the TPACK-model at present. This article proposes supplementing the TPACK-model with the knowledge components of digital cultural transformations (digitality) and, therefore, extending the TPACK-model to a DPACK-model, where D stands for digitality. Therefore, digital transformation in STEM teaching requires additional professional knowledge considering the transformation of communication, mediatization and society. Through this expansion, the focus should also be directed on the necessity that children and young people in the digitally shaped world must also be able to critically reflect on the processes of change and shape them in an ethically responsible manner. For this reason, teachers require professional knowledge to reflect, analyze, use and shape the digital transformation, which is regularly demanded of them by national and international educational standards. As a foundation of STEM teachers’ education and training, an integrated model combining these facets of knowledge and skills is provided for discussion, and, as a result, quickly found its way into the educational policy guidelines and educational science discourses in Germany. In order to integrate the sociocultural consequences of digitalization into TPACK, this paper proposes a new hemisphere, sociocultural knowledge, which extends the existing TPACK components.